TENDENCY OF PUNISHMENT OF TRAFFICKING OFFENCES IN CHINA (Revista ESMAT, 2025)
The Chinese Criminal Law of 1997 has stipulated all traffickingoffenses related to firearms, antiquities, wildlife, human beings and drugs, andincluded aggravated penalties allowing for the death penalty for all of these offenses.In the more than 20 years since then, ten Amendments have been instituted to reformand to readjust the Criminal Law in the spirit of safeguarding social harmony,assuring human rights, and carrying out a policy of severity tempered with gentleness,in accordance with emerging world trends. The Supreme Court of China has tried toguide and unify the implementation of Criminal Law and criminal policy under itsjurisdiction by publishing judiciary explanations.
Keywords: Infractions liées aux trafics illicites; Amendement de la loi pénale; Mitigation de punition; Peine capitale